Entrepreneurship Education as a Subject of Research - V. S. Nikolsky; Yu. B. Rubin; P. S. Sorokin; E. V. Morozova; I. A. Gazieva; O. S. Kharina; V. A. Lednev; M. A. Lukashenko; Yu. A. Viatskaya; E. D. Platonova (Высшее образование в России, 2023)
On April 5, 2023 a round-table discussion on “Entrepreneurship Education as a Subject of Research” was organized by the Editorial Board of the “Higher Education in Russia” Journal with the Moscow University for Industry and Finance “Synergy” in the framework of the International Scientific Congress “The Role of Business in Society Transformation – 2023”. Entrepreneurship education formation is a focus of interest as for scientists, and for practitioners as well all around the world. During a round-table there were discussed the actual research issues required attention of academic society. Research trends were defined and connected: 1) with values, identity and moral dimension; 2) with mentors’ experience; 3) with students’ experience.